Perancangan Sistem Informasi Signature Verification System For Banking - Ikrar Adinata Arin (Bina Nusantara University, 2013)
Every teller of Bank XYZ Teller needs to verify and validate the customer's signature for withdrawal transactions done at the bank in order to avoid manipulation of original signature of the customer. If the amount of withdrawals money made is very large number (typically for corporate customers), the risk of manipulation becomes higher. Therefore, there is a need to implement a kind of software applications which functions as a tool to verify the signatures of banking customers. The author conducted a Signature Verification System for businees operational of Bank XYZ.